The Antioxidant, Anti-Inflammatory and Immunomodulatory Effects of Camel Milk - Behrouz, Sepide; Saadat, Saeideh; Memarzia, Arghavan; Sarir, Hadi; Folkerts, Gert; Boskabady, Mohammad Hossein (Frontiers in Immunology, 2022)
Camel milk (CM) has been found to have several health benefits, including antiviral, antibacterial, anti-tumor, anti-fungal, antioxidant, hypoglycaemic and anti-cancer activities. In addition, CM can counter signs of aging and may be a useful naturopathic treatment for autoimmune diseases. The composition of CM varies with geographic origin, feeding conditions, seasonal and physiological changes, genetics and camel health status. In the present review, we collate the diverse scientific literature studying antioxidant, anti-inflammatory and immunomodulatory effects of CM and its bioactive compounds. The databases Scopus, PubMed, and Web of Science were searched until the end of September 2021 using the keywords: camel milk, antioxidant, anti-inflammatory, immunomodulatory. The anti-inflammatory mechanism of CM in various inflammatory disorders was consistently reported to be through modulating inflammatory cells and mediators. The common anti-inflammatory bioactive components of CM seem to lactoferrin. The antioxidant effects of α-lactalbumin, β-caseins and vitamin C of CM work by reducing or inhibiting the production of reactive oxygen species (ROS), hydroxyl radicals, nitric oxide (NO), superoxide anions and peroxyl radicals, likely alleviating oxidative stress. Higher levels of protective proteins such as lysozyme, IgG and secretory IgA compared to cow's milk, and insulin-like protein activity of CM on ß cells appear to be behind the immunomodulatory properties of CM. The evidence suggests that CM and its bioactive components has the potential to be a therapeutic treatment for diseases that cause inflammation, oxidative stress and/or immune-dysregulation.